Flank sucking in a Doberman pincher - GIANNOULOPOULOS (Γ.Δ. ΓΙΑΝΝΟΥΛΟΠΟΥΛΟΣ) G. D.; SARIDOMICHELAKIS (Μ.Δ. ΣΑΡΙΔΟΜΙΧΕΛΑΚΗΣ) M. N. (Journal of the Hellenic Veterinary Medical Society, 2017)
Flank sucking is a behavioural abnormality of compulsive nature that occurs almost exclusively in Doberman pinchers and is frequently accompanied by other abnormal behaviours, such as aerai lick dermatitis, blanket sucking and pica. A 2.5-year old, intact male, Doberman pinscher was presented because of a two-month long history of persistent right flank sucking. The dog was up-to-date with vaccinations and lived exclusively outdoors with his mother. The onset of the problem coincided with a period of crate restraining, where a short chain was used to avoid copulation with his mother, when she was in oestrus. Since then, the abnormal behaviour occurred on a daily basis and was not associated with neurological signs. In addition, the dog presented blanket sucking and pica that had first appeared during puppy hood. No clinical abnormalities were detected and the dog did not show signs of anxiety, aggression or fear during physical examination and blood sampling. Later-on and while remaining calm in the waiting room of the Clinic, the dog started chasing, chewing and sucking his right flank for over three minutes, but stopped immediately after his owner’s verbal intervention. Primary diagnosis was compulsive flank sucking; differential diagnosis included Trichuris vulpis infestation, allergic dermatitis and psychomotor seizures. Results of haematological and serum biochemical examinations were unremarkable, whereas serological examination for Leishmania and faecal parasitological examination did not reveal significant results. Suggested treatment included administration of an anthelminthic combination (praziquantel, pyrantel and febantel), orally, for 4 consecutive days and clomipramine, at the dose of 1 mg/kg of body weight, every 12 hours, orally, for a long period of time, along with instructions to avoid the causative and triggering factors. Two months later, the owner reported that, although clomipramine had not been administered, the abnormal behaviour disappeared when the dog had been relocated to a new environment with no other animals and was free to roam. However, flank sucking reappeared after the dog had been moved back to the initial environment and chained.